2021
DOI: 10.1128/mbio.03441-20
|View full text |Cite
|
Sign up to set email alerts
|

The Prophage and Plasmid Mobilome as a Likely Driver of Mycobacterium abscessus Diversity

Abstract: Mycobacterium abscessus is an emerging pathogen that is often refractory to antibiotic control. Treatment is further complicated by considerable variation among clinical isolates in both their genetic constitution and their clinical manifestations. Here, we show that the prophage and plasmid mobilome is a likely contributor to this variation. Prophages and plasmids are common, abundant, and highly diverse, and code for large repertoires of genes influencing virulence, antibiotic susceptibility, and defense aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(93 citation statements)
references
References 64 publications
6
87
0
Order By: Relevance
“…We did not attempt to identify plasmids, as short-read sequencing data are unreliable for this purpose [75]. Plasmids are likely to be another mechanism of LGT, as previous studies have identified conjugative plasmids in M. abscessus [8,[14][15][16].…”
Section: Of Lgt In M Abscessusmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not attempt to identify plasmids, as short-read sequencing data are unreliable for this purpose [75]. Plasmids are likely to be another mechanism of LGT, as previous studies have identified conjugative plasmids in M. abscessus [8,[14][15][16].…”
Section: Of Lgt In M Abscessusmentioning
confidence: 99%
“…abscessus recombines more frequently than the other subspecies [13]. M. abscessus encodes a diverse array of plasmids and prophages [8,[14][15][16]; the extent to which distinct mechanisms of lateral gene transfer (LGT) shape diversity of M. abscessus is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The genome from isolate 09–13-3 comprised a chromosome of a size of 4.949.160 bp and a plasmid of 24.978 bp. This plasmid (pMabs-09-13, plasmid map in Supplementary Figure S2 A) exhibits an identity of 99.86% (with a coverage of 100%) to plasmids pGD42-1 (accession CP065281.1), pGD69A-1 (accession CP065270.1), and pGD69B-1 (accession CP065267.1) described by Dedrick et al [ 24 ]. Supplementary Figure S2 B shows an alignment of plasmids pMabs-09-13 and pGD42-1.…”
Section: Resultsmentioning
confidence: 91%
“…The question now is whether this success can be translated into other patients with similar M. abscessus infections. We are finding that there is enormous variation among M. abscessus clinical isolates in their phage infection profiles, and it will require considerable effort to assemble a phage cocktail that acts broadly across this strain variation [ 61, 62 ]. Nonetheless, if phages can be matched to a patient’s bacterial isolate, the prospects of providing substantial clinical benefits are considerable.…”
Section: Therapeutic Potential Of Mycobacteriophagesmentioning
confidence: 99%